Direct Numerical Simulation of Incompressible Flows in a Zero-Pressure Gradient Turbulent Boundary Layer (Advances in Applied Mathematics and Mechanics, 2019)
Direct numerical simulation (DNS) of incompressible flows in azero-pressure gradient turbulent boundary layer (TBL) is conductedby a finite difference method in which a fourth order upwind schemeis applied to discretize the convective terms while a re-scalingapproach is used to set inlet flow conditions. The Reynolds numbersbased on free flow velocity and momentum thickness at the recyclesection are respectively 687, 1074, and 1430. The DNS has obtainedfavorable results indicating that the turbulence statistics are quitesatisfactory as compared with the existing numerical andexperimental results. The three dimensional turbulent structures atthe momentum thickness Reynolds number of 1430 in several differentinstants are illustrated by the iso-surface of swirl strength square(the square of imaginary part of the complex eigenvalue of velocitygradient tensor) together with velocity vectors in three differentcross sections. It is found that there are three kinds of vorticalstructures: quasi-symmetrical and asymmetrical hairpin vortices, andworm-like vortices. The DNS based on the numerical method cancertainly reveal the main characteristics of the TBL flows at thegiven Reynolds numbers.